2020
DOI: 10.1111/mice.12549
|View full text |Cite
|
Sign up to set email alerts
|

Postdisaster image‐based damage detection and repair cost estimation of reinforced concrete buildings using dual convolutional neural networks

Abstract: Reinforced concrete (RC) buildings are commonly used around the world. With recent earthquakes worldwide, rapid structural damage inspection and repair cost evaluation are crucial for building owners and policy makers to make informed risk management decisions. To improve the efficiency of such inspection, advanced computer vision techniques based on convolutional neural networks have been adopted in recent research to rapidly quantify the damage state (DS) of structures. In this article, an advanced object de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 51 publications
(73 reference statements)
0
35
0
Order By: Relevance
“…It was demonstrated that the response frequency bands, vibration modes, and their combination were learned by a deep neural network as essential characteristics that were identifiable from sensor data. Wang and Cha [55] proposed an unsupervised method using an acceleration signal that was obtained from an intact laboratory-scale three-dimensional (3D) steel bridge. The response signal vectors were normalized, and then the continuous wavelet transformation (CWT) and Fast Fourier Transformation (FFT) were applied, which were then fed to a two-dimensional (2D)-CNN autoencoder to extract essential features.…”
Section: Vibration-based Shm Through DLmentioning
confidence: 99%
“…It was demonstrated that the response frequency bands, vibration modes, and their combination were learned by a deep neural network as essential characteristics that were identifiable from sensor data. Wang and Cha [55] proposed an unsupervised method using an acceleration signal that was obtained from an intact laboratory-scale three-dimensional (3D) steel bridge. The response signal vectors were normalized, and then the continuous wavelet transformation (CWT) and Fast Fourier Transformation (FFT) were applied, which were then fed to a two-dimensional (2D)-CNN autoencoder to extract essential features.…”
Section: Vibration-based Shm Through DLmentioning
confidence: 99%
“…To obtain better performance in detecting constructionrelated objects, it is recommended to fine-tune the networks for each specific application. However, as the object detection is not the core objective of this study, interested readers are referred to several articles in the relevant literature for more details (H. Kim, Kim, Hong, & Byun, 2018;Pan & Yang, 2020;Roberts & Golparvar-Fard, 2019;Son et al, 2019).…”
Section: Object Detectionmentioning
confidence: 99%
“…With the development of deep learning, the applications of automatic defect detection on community infrastructures and built environment are increasing. CNNs have been used for rapid structural damage detection and maintenance cost estimation after a serious earthquake so as to provide a reference for owners and decision-makers to make accurate and timely risk management decisions [53]. Region-based CNN (R-CNN) and faster R-CNN have also been used for road damage detection and classification [54].…”
Section: Cnn Use For Building Deterioration Detectionmentioning
confidence: 99%